Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1128/mcb.14.9.5832-5839.1994
|View full text |Cite
|
Sign up to set email alerts
|

GSH1, Which Encodes γ-Glutamylcysteine Synthetase, Is a Target Gene for yAP-1 Transcriptional Regulation

Abstract: Changes in gene dosage of the YAP1 gene, encoding the yAP-1 transcriptional regulatory protein, cause profound alterations in cellular drug and metal resistance. Previous studies on yAP-1 action in yeast cells have used the AP-1 response element (ARE) from simian virus 40 as an artificial site for yAP-1-mediated transcriptional activation. No authentic yeast target sites for control of gene expression by yAP-1 are known. Here we show that the GSH1 gene, encoding gamma-glutamylcysteine synthetase, is transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…36,37 The Yap1 transcription factor is involved in GSH1 transcription activation and increases the expression of SOD1 and CAT1 genes after exposure to H 2 O 2 . 38,39 Yap1 was also demonstrated to regulate ATP-binding cassette (ABC) transporters in yeast. Members of the ABC superfamily catalyze the ATP-dependent transport of chemically diverse compounds across cellular membranes, including the plasma membrane or intracellular organellar membranes.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 The Yap1 transcription factor is involved in GSH1 transcription activation and increases the expression of SOD1 and CAT1 genes after exposure to H 2 O 2 . 38,39 Yap1 was also demonstrated to regulate ATP-binding cassette (ABC) transporters in yeast. Members of the ABC superfamily catalyze the ATP-dependent transport of chemically diverse compounds across cellular membranes, including the plasma membrane or intracellular organellar membranes.…”
Section: Discussionmentioning
confidence: 99%
“…However, both drugs are not classified as the chemicals provoking oxidative stress. On the other hand, both GSH1 and GSH2 , coding for γ-glutamylcysteine synthetase and glutathione synthetase, respectively, which are the enzymes responsible for GSH biosynthesis, are among the Yap1 targets ( , ). GSH functions as an antioxidant by supplying electrons to the glutathione peroxidase reaction.…”
Section: Discussionmentioning
confidence: 99%
“…68 The presence of two cysteine rich clusters that respond preferentially to different types of stress suggests that the type of Yap1 cysteine modification has downstream implications on gene regulation. Indeed, hydrogen peroxide activated Yap1 up-regulates the expression of genes whose products include antioxidants and components of thiol-reducing pathways including TRX2, 159 γglutamylcysteine synthetase (GSH1), 160 glutathione reductase (GLR1), 161 and cytosolic catalase T (CTT1). 68 It has been demonstrated that yeast deficient in the SKN7 gene are also hypersensitive to oxidative stress, 162 underscoring the complexity of overlapping molecular defenses against oxidative stress.…”
Section: Chemical Research In Toxicologymentioning
confidence: 99%